Linearizing techniques for sensor output - Saddiqi, Mohammad Tahir; Khan, Sheroz; Saddiqi, Ummer (IIUM Press, 2011)
Sensors are fundamental part of circuit performing measurement as well as control in various fields. They present the measured quantity in analog electrical signal which is processed to perfonn the desired operation. Most of the signal processing nowadays is in digital domain due to advantages like noise-insensitivity, more robustness, better production yield, reliability and testability. To bring all these merits into real world applications, it is desirable to convert analogue signals output of sensor into digital domain representation. But due to non-linearity of the sensor output the digital approximation of actual physical signal is erroneous and does not correspond to the actual measured quantity. This chapter discuss about various methods for linearizing the output of the sensors.